Design And Construction Of A 3-Axis Computer Numerical Control Plasma Arc Cutting Machine With Mach3 Controller - Putra, I Kadek Dana; Chandra, Dimas Surya Aldi; Nata, Agus Surya Mahendra; Partha, Cokorde Gede Indra; Agung, I Gusti Agung Putu Raka (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2024.v23i02.P03, 2024)
This study investigates the design of a CNC machine with a MACH 3 controller and a floating Z-axis to enhance efficiency and precision in the cutting process of iron plates, particularly for the production of laundry machine bodies at Adhi Teknik, a small and medium-sized enterprise (SME) in Bali. The research methodology includes observations and experiments conducted at the Adhi Teknik Workshop and the Laboratory of the Electrical Engineering Study Program. The test results show that the designed CNC machine is able to work optimally with high movement accuracy with an error value of 0.00315% to 0.0125%.  The use of electrical energy of CNC machines tested on 304 stainless plate workpieces with a thickness of 1 mm has an average of 104 to 718 Wh on plasma and compressor control systems. The cutting error for basic patterns ranges from 0% to 0.266%, and for additional patterns, it ranges from 0.66% to 0.518%. Based on the research results, the designed CNC machine successfully improves cutting efficiency and precision. Further development could include the creation of a knockdown frame, the use of hard gears, an inverter blowback system, and the addition of a water tank.